2002
DOI: 10.3354/dao048163
|View full text |Cite
|
Sign up to set email alerts
|

Iridovirus disease in two ornamental tropical freshwater fishes: African lampeye and dwarf gourami

Abstract: Many species of ornamental freshwater fishes are imported into Japan from all over the world. We found African lampeye Aplocheilichthys normani and dwarf gourami Colisa lalia suffering from an iridovirus infection just after being imported by tropical fish wholesalers from Singapore. African lampeye were cultured on the Indonesian Island of Sumatra and dwarf gourami were cultured in Malaysia before export. Diseased fishes displayed distinct histopathological signs of iridovirus infection: systemic appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 19 publications
7
88
0
2
Order By: Relevance
“…However, in contrast to tropical iridovirus-infected cells, in TGIV-infected cells there is no apparent slit or membranous structure separating the viromatrix from the cytoplasm as sometimes seen in tropical virus infections (Sudthongkong et al 2002b). The nuclei of TGIV-infected cells disintegrated before the viromatrix was fully established in the cytoplasm; however, the nuclei was displaced to one side in tropical iridovirus-infected cells, even when the inclusion bodies occupied most of the cytoplasm , Sudthongkong et al 2002a. The most striking difference is that the eosinophilic enlarged cells in tropical iridovirus infections are ballooning, degenerated cells with few remaining virions in their inclusion bodies, while in TGIV-infected cells all the eosinophilic enlarged cells observed were phagocytes containing cell debris.…”
Section: Discussionmentioning
confidence: 94%
“…However, in contrast to tropical iridovirus-infected cells, in TGIV-infected cells there is no apparent slit or membranous structure separating the viromatrix from the cytoplasm as sometimes seen in tropical virus infections (Sudthongkong et al 2002b). The nuclei of TGIV-infected cells disintegrated before the viromatrix was fully established in the cytoplasm; however, the nuclei was displaced to one side in tropical iridovirus-infected cells, even when the inclusion bodies occupied most of the cytoplasm , Sudthongkong et al 2002a. The most striking difference is that the eosinophilic enlarged cells in tropical iridovirus infections are ballooning, degenerated cells with few remaining virions in their inclusion bodies, while in TGIV-infected cells all the eosinophilic enlarged cells observed were phagocytes containing cell debris.…”
Section: Discussionmentioning
confidence: 94%
“…data). In ornamental freshwater fishes, megalocytivirus has also been isolated from diseased African lampeye Aplocheilichthys normani, which were cultured on Sumatra Island and exported to Japan (Sudthongkong et al 2002a), and diseased dwarf gourami Colisa lalia, which were exported to Australia from southeast Asia (Go & Whittington 2006). Moreover, megalocytivirus diseases have also been found in both marine and freshwater fishes in other Asian countries (Inouye et al 1992, Chua et al 1994, Matsuoka et al 1996, Danayadol et al 1997, Kasornchandra & Khongpradit 1997, Chou et al 1998, Jung & Oh 2000, Chao et al 2002, Sano et al 2002, Sudthongkong et al 2002b, Weng et al 2002, Chen et al 2003, GibsonKueh et al 2003, Shi et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia iridovirus-like virions from dwarf gourami Colisa lalia imported from Singapore (Anderson et al 1993) were reported in 1988, and in 2006 Murray cod iridovirus (MCIV) from intensively farmed Murray cod Maccullochella peelii peelii was observed there ; Armstrong & Ferguson (1989) reported an iridovirus in chromide cichlid Etroplus maculatus in Canada, also imported from Singapore; and Sudthongkong et al (2002) reported outbreaks of African lampeye Aplocheilichthys normani iridovirus (ALIV) and dwarf gourami C. lalia iridovirus (DGIV) in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Iridoviruses have been associated with severe mortality and economic loss in freshwater ornamental fish, including angelfish Pterophyllum scalare, gourami Trichogaster spp., swordtail Xiphophorus hellerii, dwarf gourami Colisa lalia, chromide cichlid Etroplus maculatus, guppy Poecilia reticulata, doctor fish Labroides dimidatus, mollies Poecilia latipinna and African lampeye Aplocheilichthys normani (Armstrong & Ferguson 1989, Anderson et al 1993, Hedrick & McDowell 1995, Rodger et al 1997, Paperna et al 2001, Sudthongkong et al 2002, as well as in a wide variety of marine fish species (Inouye et al 1992, Bloch & Larsen 1993, Chua et al 1994, Matsuoka et al 1996, Jung & Oh 2000. Such iridoviruses are becoming ubiquitous due to transfer of ornamental fish by international trade.…”
Section: Introductionmentioning
confidence: 99%